Pengalaman Pasien dalam Pemanfaatan Layanan Rawat Jalan di Poliklinik Bedah RSUD S. K. Lerik Kota Kupang - Triyanti Seran; Dominirsep O. Dodo; Masrida Sinaga (Yayasan Literasi Sains Indonesia, 2024)
Patient experience is a valuable experience evaluation of a person's satisfaction with processes and services from the patient's perspective. Based on Google user reviews regarding RSUD S. K. Lerik, Kupang City, some complained about poor online registration, long waiting times which resulted in a patient suffering from gastric disease having to be treated in the ER unit. Initial observations on 15-17 November 2022 revealed that there was a delay in service. This study aims to explore the experiences of outpatients regarding services at the S. K. Lerik Regional Hospital, Kupang City. This research is of a qualitative type with a phenomenological research model. There were eight informants in this study who were taken using purposive sampling techniques. The results of research on seven aspects, namely access, patient feelings, treatment, attitudes of health workers, support, obstacles and hopes, show two categories of experience. First, the experience that is categorized as good is easy access to facilities, a clean and safe environment, good communication between medical personnel and patients, medical personnel always maintain hand hygiene, fast examination times, patients receive emotional support. Second, experiences that were categorized as poor were BPJS patients buying infusion fluids and gauze at their own expense, patient communication with inpatient staff was poor, TVs were not used, waiting times were long, and services did not start on time. It is hoped that RSUD S. K Lerik, Kupang City can improve the quality of service for a better patient experience when utilizing health services.